Misfortunes of the moment: Italy and the Supreme War Council in World War I - Innocenti, Claudio Roberto (Kansas State University, 2018)
The history of Italy during World War I has often been characterized by the eleven bloody and inconsequential battles on the Isonzo River from 1915 to 1917. The twelfth battle, Caporetto, was one of the most lopsided defeats of the war. The subsequent development of an inter-Allied Supreme War Council has often been portrayed as a British and French creation with little Italian input. However, the defeat at Caporetto actually signified the rapid escalation of Italy’s influence among her Allies. Combined with American tentativeness and Russian collapse, the winter of 1917-1918 offered key Italian leaders the opportunity to manipulate debates on Allied strategy. Ultimately, the Italians could not keep true to the promises they made during a succession of inter-Allied conferences. This failure led to indecision by Italian leaders during the critical campaigns of 1918 and disillusionment in Italy itself during the post-war era.
Keywords: Caporetto; ItalySupreme War Council